Linha ocupada, cliente livre!: um estudo sobre contact centers e fidelidade dos clientes de operadoras de telefonia celular - Rabia, Selim (2008)
This study approaches the influence of the interaction between customers and cellular companies in the customer loyalty using the contact center as the way of interaction between them. That interaction if well managed can be a relevant competitive advantage in a world where innovations and its dissemination are very fast. On the contrary, a bad managed relationship between customer and companies may result in customer disloyalty and change of supplier. To evaluate the costumer satisfaction about their interaction with the cellular companies it was carried out a survey by sending e-mails to São Paulo State customers and receiving their answers through a specific web address. In order to analyze the subject it was applied theories of service marketing, relationship marketing and market orientation as well as contact center (or call center) and loyalty literature. That survey considered three main areas: market orientation, contact center service quality and customer loyalty. Statistical techniques of factor analysis and cluster analysis were applied to analyze the results. It was also elaborated a comparative analysis of loyalty for the main companies and a simulation in order to estimate the potential losses of customers. The results show big customer dissatisfaction about the cellular companies regarding to subjects that are more relevant to them as receiving answer to their needs and about the contact center efficiency. The customers also show a strong tendency to disloyalty. Considering the cellular phone number portability in 2009, when the customer will be allowed to change the supplier but, at the same time, maintaining his phone number, the risk of lose customers is bigger for companies because in that case 64% of the customer declared his/her disloyalty. The relevance of this study for organizations is that it shows that it is possible to notice the contact center as a customer satisfaction generation point, as well as a competitive differentiation tool that seems to be not sufficiently considered by marketing practitioners.